Peran Kualitas Informasi Terhadap Keputusan Investasi Syariah Generasi Z Dengan Dimoderasi Media Informasi Era Covid-19 - Yuli Dahlia Saputri; Erike Anggraeni; Madnasir Madnasir (Jurnal Ilmiah Ekonomi Islam, 2023)
The Covid-19 pandemic has proven to have a significant impact on Islamic investment instruments in the Islamic capital market. However, Islamic investment in the Islamic capital market was able to record positive things even in the midst of the Covid-19 pandemic. Not only that, with the largest Muslim population in the world and supported by the bright prospects for the Indonesian Islamic capital market in the next few years, the Islamic capital market will attract more investors. Sharia investment is a very important issue, especially for Generation Z. in Lampung Province. This research was conducted with the aim of looking at the important role of information quality in sharia investment decisions as well as being moderated by the information media, whether the information media is able to strengthen or weaken the relationship to sharia investment decisions in Generation Z in the Covid-19 era. This research includes quantitative research with a moderation approach. The research was conducted in Lampung Province during the Covid-19 era. The data used is primary data obtained from Generation Z Muslim investors in Lampung Province using a questionnaire sent via the Google form application. The sampling technique used was purposive sampling. Data analysis using SmartPLS 3.0. The results of the study show that the quality of information has an influence on sharia investment decision-making in Generation Z in the Covid-19 era. Investment information media strengthens the influence of information quality on sharia decision-making in Generation Z in the Covid-19 era.